Role of hypoxia in the tumor microenvironment and targeted therapy - Chen, Gaoqi; Wu, Kaiwen; Li, Hao; Xia, Demeng; He, Tianlin (Frontiers in Oncology, 2022)
Tumor microenvironment (TME), which is characterized by hypoxia, widely exists in solid tumors. As a current research hotspot in the TME, hypoxia is expected to become a key element to break through the bottleneck of tumor treatment. More and more research results show that a variety of biological behaviors of tumor cells are affected by many factors in TME which are closely related to hypoxia. In order to inhibiting the immune response in TME, hypoxia plays an important role in tumor cell metabolism and anti-apoptosis. Therefore, exploring the molecular mechanism of hypoxia mediated malignant tumor behavior and therapeutic targets is expected to provide new ideas for anti-tumor therapy. In this review, we discussed the effects of hypoxia on tumor behavior and its interaction with TME from the perspectives of immune cells, cell metabolism, oxidative stress and hypoxia inducible factor (HIF), and listed the therapeutic targets or signal pathways found so far. Finally, we summarize the current therapies targeting hypoxia, such as glycolysis inhibitors, anti-angiogenesis drugs, HIF inhibitors, hypoxia-activated prodrugs, and hyperbaric medicine.